The Effectiveness of Trunk and Balance Warm-up Exercises in Prevention, Severity, and Length of Limitation From Overuse and Acute Lower Limb Injuries in Male Volleyball Players - Yuki Muramoto; Hironobu Kuruma (International Journal of Sports Physical Therapy)
# Background